2016
DOI: 10.1038/srep34704
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histone acetylation on superoxide dismutase 1 gene expression in the pathogenesis of senile cataract

Abstract: Histone acetylation plays key roles in gene expression, but its effects on superoxide dismutase 1 (SOD1) expression in senile cataract remains unknown. To address this problem, the study was to investigate the influence of histone acetylation on SOD1 expression and its effects in the pathogenesis of senile cataract. Senile cataract was classified into three types—nuclear cataract (NC), cortical cataract (CC), and posterior subcapsular cataract (SC)—using the Lens Opacities Classification System III. In senile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…A previous study from our group found that the decrease of histone acetylation at the SOD1 promoter is associated with the decrease of SOD1 expression in age-related cataracts. Histone acetylation has an important role in regulating SOD1 expression which participate in the pathogenesis of age-related cataracts [9]. In our study, trichostatin A (TSA, an HDAC inhibitor) corrected the anacardic acid (AA, an HAT inhibitor)-induced imbalance between HATs and HDACs, resulting in enhancing SOD1 expression by reversing histone acetylation.…”
Section: Introductionmentioning
confidence: 73%
“…A previous study from our group found that the decrease of histone acetylation at the SOD1 promoter is associated with the decrease of SOD1 expression in age-related cataracts. Histone acetylation has an important role in regulating SOD1 expression which participate in the pathogenesis of age-related cataracts [9]. In our study, trichostatin A (TSA, an HDAC inhibitor) corrected the anacardic acid (AA, an HAT inhibitor)-induced imbalance between HATs and HDACs, resulting in enhancing SOD1 expression by reversing histone acetylation.…”
Section: Introductionmentioning
confidence: 73%
“…Oxidative stress Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry has long been accepted as an initiating factor in the aetiology of nuclear ARC [40]. Normal function of lenses depends on the balance among oxidative stress, antioxidant protection and repair processes [15,40]. Accumulation of reactive oxygen species (ROS) and/or the lack of nuclear glutathione (GSH) could induce apoptosis and lead to the development of nuclear ARC [5,41].…”
Section: Discussionmentioning
confidence: 99%
“…Critical enzymes involved in DNA methylation, such as DNMT1 and MeCP2, have been identified in human lens epithelial cells (HLECs) [10,11]. Epigenetic regulatory processes, including DNA methylation of CRYAA [9,10,[12][13][14], histone acetylation of SOD1 [15] and long non-coding RNA (lncRNA)-MIAT and KCNQ1OT1 [16,17], have been implicated in the pathological cataractogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The median values of STT1 were 25.00 mm/min (range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] for the control group and 2.90 mm/min (range, 0-9) for the KCS group (P < .001). In relation to the TBUT, the median values were 10.00 seconds (range, 1-25) for the control group and 0.00 second (range, 0-8) for the KCS group (P < .001).…”
Section: Tear Productionmentioning
confidence: 99%
“…19,22,23 Senile cataract, diabetic retinopathy, macular degeneration, and autoimmune uveoretinitis are examples of diseases associated with remodeling of chromatin in ocular cells. [24][25][26][27][28][29] Nuclear size and shape, DNA content (ploidy), and chromatin remodeling can be studied in cytological preparations using video image analysis and the Feulgen reaction. 20,30 Video image analysis in Feulgen-stained preparations is recommended to evaluate defined cell populations.…”
Section: Introductionmentioning
confidence: 99%